Biduality in Spaces of Holomorphic Functions - Galindo, Pablo; Maestre, Manuel; Rueda, Pilar (MATHEMATICA SCANDINAVICA, 2000)
This paper contains characterizations of the bidual space of some closed subspaces of H_b(U), the space of holomorphic functions bounded type defined on an open subset U of a Banach space X, where U is either a bounded balanced open set or the whole space X.